ANALISIS FAKTOR MAKROEKONOMI TERHADAP VOLUME PERDAGANGAN SUKUK NEGARA RITEL SERI 016 - Mustofa, Nur Wahid; Ardiansyah, Okky Vian; Maharani, Sintya Puan; Kumalasari, Silva Indria; Diniati, Bintis Ti'anatud (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study analyzes the impact of macroeconomic factors on the trading volume of SR016 Retail Sukuk in Indonesia's secondary market from June 2022 to February 2025. The research examines five independent variables: inflation, sukuk yield, sukuk price, rupiah exchange rate against USD, and BI Rate, using multiple linear regression analysis with monthly time series data. This research analysis uses eviews 13 software. The findings reveal that only the BI Rate has a significant negative effect on SR016 trading volume, with a coefficient of -2.764297 (sig. 0.0284), indicating that higher interest rates lead to decreased sukuk trading activity. Meanwhile, inflation, sukuk yield, sukuk price, and the rupiah exchange rate show no significant individual impact on trading volume. However, these macroeconomic factors collectively explain 36.18% of sukuk trading volume variations when tested simultaneously (F-stat 4.174927, sig. 0.007601). These results suggest that retail sukuk investors in Indonesia primarily adopt a buy-and-hold strategy, with limited sensitivity to short-term macroeconomic fluctuations except for central bank policy rates. The study contributes to understanding Islamic financial market dynamics in Indonesia and provides insights for regulators and market participants to develop more effective strategies for enhancing secondary market liquidity.